Observational Evidence of Instability Phenomena Related to Open Star Clusters Based on Gaia Data - Kovaleva, D. A.
The vast amount of high-quality astrometric and photometric data from Gaia space mission opened new prospects in the investigation of the population of galactic star clusters. In particular, a number of observational evidence have emerged in relation to the phenomena of instability that previously were mainly predicted by dynamical simulations. These are signs of former violent relaxation, ongoing tidal disruption, interaction between the clusters and results of disruption of the clusters. We discuss methods of discovery of such evidence along with some interesting examples.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture